Pemantauan Penyerapan Gas Beracun Menggunakan Tanaman Sansevieria Pada Ruangan Tertutup - Barzan Trio Putra; Kemahyanto Exaudi; Rossi Passarella; Purwita Sari (Komputika : Jurnal Sistem Komputer, 2022)
Indoor air quality needs special attention because it is very influential on human health. One way that can be done is to keep the indoor air quality clean by utilizing sansevieria trifasciata plants. This study aims to detect air pollution levels in a closed room containing the Sansevieria Trifasciata plant. The plant functions as an absorbent of toxic gases such as carbon monoxide (CO) contaminated indoors. The prototype test room measures 65cm x 65cm x 65cm. Gas sensors are placed at the top of the room and slots to insert gas samples at the front. The working system in the room is sterilized until the gas sensor detects the normal ppm value, then the gas sample is inserted into the test room using injectable media and the gas sensor re-reads the ppm value until normal conditions. The results prove that sansevieria plants can absorb CO gas perfectly. The size and shape of sansevieria also affect the absorption process of CO gas. the bigger the plant, the better the absorption. This is evidenced by the average time it takes a small sansevieria to absorb smoke gas until it reaches normal ppm is 120 minutes. As for the big sansevieria for 80 minutes.